A review of the migration mechanisms of microplastics in terrestrial environments - Yu, Hui; Zhang, Weiqing; Zheng, Lixia; Li, Tong; Hai, Chunxing; Wang, Yong; Lyu, Tao (Korean Society of Environmental Engineering, 2024)
Microplastic (MP) release into the terrestrial environment has occurred since humans started manufacturing and using plastics. These tiny plastic particles can be found in various media, including the atmosphere, soil, freshwater, sediments, and organisms. MPs migrate through terrestrial environmental media due to wind, water, gravity, and biological processes. Although the variables that affect the migration process have been investigated in various settings, the mechanisms of MP migration in terrestrial environments have yet to be systematically characterized. This study classifies the migration mechanisms of MPs as physical, chemical and biological manners, and discusses the factors affecting migration mechanisms in dynamic factors, environmental factors and MP characteristics. Examining the action mechanisms of migration can establish a foundation for understanding the migration processes of MPs and provide a theoretical framework for modeling MP movement in environmental. Future research challenges include understanding the effect of MP characteristics in the migration process and simulating the migration of MPs in the environment in the long-term. Exploring the MP migration on various spatial and temporal scales, considering the life cycle of MPs is a worthy research direction.
Keywords: Mechanical migration; Microplastics; Terrestrial environments